Seasonal Dependent Impact of Ice Cloud Longwave Scattering on the Polar Climate - Chen, Yi‐hsuan; Huang, Xianglei; Yang, Ping; Kuo, Chia‐pang; Chen, Xiuhong (Geophysical Research Letters, 2020)
Most climate models neglect cloud longwave (LW) scattering because scattering is considered negligible compared to strong LW absorption by clouds and greenhouse gases. While this rationale is valid for simulating extrapolar regions, it is questionable for the polar regions, where the atmosphere is dry and hence has weak absorption, and ice clouds that have strong scattering capability frequently occur. Using the slab- ocean Community Earth System Model, we show that ice cloud LW scattering can warm winter surface air temperature by 0.8- 1.8Â K in the Arctic and 1.3- 1.9Â K in the Antarctic, while this warming becomes much weaker in polar summer. Such scattering effect cannot be correctly assessed when sea surface temperature and sea ice are prescribed as this effect is manifested through a surface- atmosphere coupling. Cloud LW scattering is a necessity for the correct simulation of polar climate and surface radiation budget, especially in the winter.Plain Language SummaryCloud longwave scattering has never been deemed as a necessity in climate models. Out of all climate models in the IPCC fifth and sixth assessments, only three modeling centers have longwave scattering included in their models. Our study explained why the traditional wisdom of neglecting longwave scattering breaks down for the simulation of high- latitude climate in the fully coupled models. We showed the critical importance of atmosphere- surface radiative coupling for correctly assessing the role of cloud longwave scattering in the model simulation of climate mean state as well as climate changes, an issue overlooked by all previous studies. We argued that the cloud longwave scattering is a necessity in climate models, not an option.Key PointsCloud longwave scattering is more important in the polar regions than the extrapolar regionsBy surface- atmosphere radiative coupling, cloud longwave scattering can warm the polar surface, more in the winter than in the summerCloud longwave scattering is a necessity instead of an option for correctly ...